ANALYSIS OF HISTORY TEXTBOOKS ON THE SCIENCE OF ANCIENT MESOPOTAMIAN ZIGGURAT ARCHITECTURE - Algandi Algandi; Nur Syafarudin (PT. Jurnal Center Indonesia Publisher, 2026)
This article aims to analyze the scientific content in the field of Ancient Mesopotamian ziggurat architecture presented in the History textbook of the 2009 School-Based Curriculum by Tarunasena M. This study uses a qualitative approach with a content analysis method to examine historical discourse related to the development of science, technology, and civilization in Mesopotamia, especially in the Sumerians, Assyrians, and Chaldeans. The results of the Analysis show that the narrative in the textbook has included a representation of the progress of Mesopotamian civilization through orderly urban planning, the use of clay building materials, mastery of arithmetic and geometry, metal processing, the construction of ziggurats as religious and political symbols, the establishment of libraries as centers of knowledge, and the creation of monumental architectural works such as the Hanging Gardens of Babylon. These findings indicate that textbooks play an important role in transmitting to students the values of scientific progress, innovation, and the heritage of civilization.